A Study on the Species Composition of Necrophagous Dipteran Flies Infesting Beef Meat in Urban and Rural Location in Kota Bahru. - Baharuddin, Nurul Najwa (Universiti Sains Malaysia, 2016)
The objective of this study is to identify the species variation among the necrophagous dipteran flies that infest exhibiting preference to two different habitats namely urban and rural locations. The animal model used was 500 g of fresh beef meat and the research was conducted using USM Health Campus as representing urban location and Kg Keledang, Beta as representing rural location. Three sets of experiments were conducted in each location with two samples each. The animal models were inspected every 2 hours until opposition and then twice every day. The presence of eggs, larvae, pupae and the adult's flies were recorded during the observations and taxonomical identification was conducted following the standard taxonomical keys. About 1,229 specimens were collected in both locations. Two species namely, Chrysomya megacephala (248 specimens) and Chrysomya rufifacies (263 specimens) were identified in urban location. Whereas in the rural location in addition to Chrysomya megacephala (307 specimens) and Chrysomya rufifacies (305 specimens), 103 specimens belonging to Sarcophagidae family were also identified. The total number of specimen for both C. megacephala and C. rufifacies in urban and rural locations were nearly the same. This suggests that there is simple correspondence in number between both species composition. The specific difference found in this study was that Sarcophagidae flies were completely absent in the urban location while they were abundantly present in the rural location.